Environmental Conservation through Study Value of Bali Aga Tenganan Pegringsingan Community Culture - Wijana, Nyoman; Setiawan, I Gusti Agung Nyoman; Mulyadiharja, Sanusi; Wesnawa, I Gede Astra; Rahmawati, Putu Indah (Universitas Pendidikan Ganesha, 2020)
This research aimed to know the implementation of environmental conservation in terms of cultural value orientation, including humanistic nature orientation, man-nature orientation, time orientation, activity orientation, and relational orientation. The population of this research was the entire community in traditional village Tenganan Pegringsingan, Karangasem, Bali. This research sample amounted to 25 people, consisting of the conventional village apparatus, community leaders, and the general public. Methods of data collection were the method of observation, interview, questionnaire, and checklist. The collected data were analyzed descriptively. This research indicated that the orientation of cultural values of humanistic nature orientation and man-nature orientation had an excellent quality. The time orientation, activity orientation, and relational orientation parameters had good quality. Culture in the study community generally showed a positive thing, so the impact of culture on the quality of the environment, in general, was excellent. The results of observations in the field revealed that there were all community activities at Tenganan Pegringsingan that could not cause environmental pollution. Therefore, the role of traditional regulation or awig-awig to regulate environmental and social-culture.